The Orange Economy, Nollywood, and Decoloniality: A Critical Appraisal - Pemberton, Chantel A. (European Journal of Science, Innovation and Technology, 2023)
Nigeria’s Nollywood has evolved into a significant cultural and economic force in Africa and the world. It is renowned for its abundant production of movies, ranking second in the number of films produced annually, surpassing Hollywood and trailing Bollywood. In terms of revenue, it ranks third globally. Its popularity has gained international recognition. However, Nollywood has not managed to transcend the coloniality of its being and repertoire. Hence, this article adopts a corrective and emancipatory agenda to present a discourse on the coloniality of the application of the Orange Economy concept to Nollywood as well as the imperative of applying a decolonial epistemic regime to the operations of Nollywood. This is aimed at engendering the transformation along more decolonial and equalitarian lines of the growing exploitative stranglehold on Nollywood by non-state financial entities that exploit individuals within the Nollywood industry.